2015
DOI: 10.2208/jscejpe.71.19
|View full text |Cite
|
Sign up to set email alerts
|

Study of Mix Proportion and Quality Control of Porous Concrete Pavement Used on Urban Expressway Tunnel

Abstract: 2 正会員 阪神高速道路株式会社建設事業本部堺建設部(〒590-0075 堺市堺区南花田口町2-3-20-5F) 3 正会員 阪神高速道路株式会社建設事業本部大阪建設部(〒552-0007 大阪市港区弁天1-2-1-1900) 4 正会員 阪神高速道路株式会社技術部(〒541-0056 大阪市中央区久太郎町4-1-3-12F) 5 正会員 鹿島道路株式会社関西支店技術試験所 (〒618-0081 京都府乙訓郡大山崎町字下植野小字山王前17番) 6 正会員 鹿島道路株式会社 技術研究所(〒182-0036 東京都調布市飛田給2-19-1) 阪神高速道路淀川左岸線正蓮寺川トンネルでは,トンネル坑口から最初のカーブまでは,路面の雨水の 滞水を排除し,カーブ区間のスリップを防止する目的でポーラスコンクリート(POC)舗装を採用した. POC舗装は,大型車の多い高速道路の本線部において,12,000m 2 の大規模な施工実績はなく,重交通に 対しての十分な強度と耐久性および路面のすべり抵抗性等が要求される.POC舗装の包括的な検討として POC舗装の照査すべき性能を検討し,粗骨材種類,水結合比および空隙率などを変化させて詳細… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…They found that the Cantabro test resulted good repeatability and lowest variation. Yoshiko Takada et al [28] (2015) investigated the effect of changes the mix proportion on the strength and abrasion resistance of PCP and concluded that the change in W/C ratio did not contribute to Cantabro loss. The test methods used in their investigation were Cantabro test and wear test.…”
mentioning
confidence: 99%
“…They found that the Cantabro test resulted good repeatability and lowest variation. Yoshiko Takada et al [28] (2015) investigated the effect of changes the mix proportion on the strength and abrasion resistance of PCP and concluded that the change in W/C ratio did not contribute to Cantabro loss. The test methods used in their investigation were Cantabro test and wear test.…”
mentioning
confidence: 99%